13-93 bioactive glass/alginate composite scaffolds 3D printed under mild conditions for bone regeneration. Issue 20 (17th February 2017) - Luo, Guilin; Ma, Yufei; Cui, Xu; Jiang, Lixin; Wu, Mingming; Hu, Yang; Luo, Yanfeng; Pan, Haobo; Ruan, Changshun
Abstract : Composite scaffolds of type 13-93 bioactive glass (13-93 BG) and sodium alginate (SA), denoted 13-93 BG/SA, in mass ratios of 0 : 4, 1 : 4, 2 : 4 and 4 : 4 were prepared for bone regeneration by 3D printing under mild conditions. Abstract : Composite scaffolds of type 13-93 bioactive glass (13-93 BG) and sodium alginate (SA), denoted 13-93 BG/SA, in mass ratios of 0 : 4, 1 : 4, 2 : 4 and 4 : 4 were prepared for bone regeneration by 3D printing under mild conditions. All obtained scaffolds were completely interconnected. As the 13-93 BG/SA mass ratio increased from 0 : 4 to 4 : 4, the pore size improved from 340 ± 27 to 530 ± 27 μm, porosity increased from 65.5 ± 5.3 to 87.5 ± 3.9% and shrinkage ratios decreased by half. Moreover, 13-93 BG incorporation improved the compressive strength and modulus of the SA scaffold, achieving highest values of 16.74 ± 1.78 MPa and 79.49 ± 7.38 MPa, respectively, in 13-93 BG/SA with a 2 : 4 mass ratio. Furthermore, in vitro apatite mineralization, the release of bioactive ions (Mg 2+ and SiO4 4− ) and a weakly alkaline pH were exhibited by scaffolds containing 13-93 BG, which further promoted the attachment, proliferation and osteogenic differentiation of rBMSCs on composite scaffolds. As a result, 3D-printed 13-93 BG/SA scaffold was an ideal candidate for bone regeneration.